Private Participation in Forest Plantation Development in Nigeria (2001)
"Nigeria’s endowment of natural forest was so vast that it was thought to be inexhaustible. Today the resource base has been badly eroded. Only about 5% of the nation's land area is under forest cover. The current situation is that the nation can no longer meet its domestic wood need and has thus have to rely on wood importation to supplement domestic production. Though series of efforts have been made to bridge the gap via plantation establishment; the results of these efforts have not been good enough to achieve the objective. This paper traces the history of forest plantation establishment in Nigeria form the early part of the 19th century to date. It is observed that the level of private participation in forestry development in the country is still very low. This is contrary to the contemporary global trend in which private participation in plantation development is growing rapidly. It is suggested that public enlightenment; legislative reforms, provision of technical and financial assistance; funding of relevant research targeted at the private sector's needs and prevision of clear definition of property rights be embarked upon by the government in order to stimulate the interest of private investors."